Characterization of the Conjugation Pattern in Large Polysaccharide–Protein Conjugates by NMR Spectroscopy. (19th October 2017) - Giuntini, Stefano; Balducci, Evita; Cerofolini, Linda; Ravera, Enrico; Fragai, Marco; Berti, Francesco; Luchinat, Claudio
Abstract: Carbohydrate‐based vaccines are among the safest and most effective vaccines and represent potent tools for prevention of life‐threatening bacterial infectious diseases, like meningitis and pneumonia. The chemical conjugation of a weak antigen to protein as a source of T‐cell epitopes generates a glycoconjugate vaccine that results more immunogenic. Several methods have been used so far to characterize the resulting polysaccharide–protein conjugates. However, a reduced number of methodologies has been proposed for measuring the degree of saccharide conjugation at the possible protein sites. Here we show that detailed information on large proteins conjugated with large polysaccharides can be achieved by a combination of solution and solid‐state NMR spectroscopy. As a test case, a large protein assembly, l ‐asparaginase II, has been conjugated with Neisseria meningitidis serogroup C capsular polysaccharide and the pattern and degree of conjugation were determined.